A MOF-armored zinc-peroxide nanotheranostic platform for eradicating drug resistant bacteria via image-guided and in situ activated photodynamic therapy. (August 2022) - Huang, Kai; Li, Fupeng; Yuan, Kai; Yang, Yiqi; Chang, Haishuang; Liang, Yakun; Yan, Xuzhou; Zhao, Jie; Tang, Tingting; Yang, Shengbing
Highlights: In-situ activated PDT strategy was developed to eradicating drug resistant bacteria via Image-guided way. A novel nanoscale ZnO2 @ZIF-67 core shell structure was synthesized. A combination of enhanced CDT and PDT strategy was adopted to combat drug resistant bacteria. Abstract: The development of nanotheranostic agents is attracting attention as an innovative strategy to synergistically detect bacterial infection and eliminate bacteria. A novel MOF (ZIF-67)-armored zinc peroxide core–shell structure with a loaded organic NIR probe (ONP) is reported herein. These nanomaterials serve as "reactive oxygen species factories" that eradicate drug resistant bacteria with image guided and in situ activated photodynamic therapy (PDT). The up-regulated levels of ONOO − at infected sites can be detected by the ONP. ONP could react with ONOO − generating MB as an imaging agent and as a photosensitizer. The ZnO2 @ZIF-67(ZZ) nanogenerator simultaneously generates O2 and H2 O2 in an infected, weakened acidic microenvironment. The PDT can be applied on-demand to eliminate bacteria depending on illumination of the probe. The in situ activated PDT strategy can effectively exterminate drug-resistant bacteria, using small amounts of nanomaterials, with no obvious adverse effects in vitro and in vivo. The ONP@ZnO2 @ZIF-67(ONP@ZZ) nanoagent simultaneously eliminates drug-resistant bacteria, reduces inflammation, and accelerates wound healing. This novel nanotheranostic agent can act as an effective antibacterial platform by integrating infection detection and bacterial eradication synergistically, and bring new light for the increasingly severe challenge of drug-resistant bacteria in clinic.